High Electron Mobility in [1]Benzothieno[3,2-b][1]benzothiophene-Based Field-Effect Transistors: Toward n-Type BTBTs - Usta, Hakan; Kim, Dojeon; Ozdemir, Resul; Zorlu, Yunus; Kim, Sanghyo; Ruiz Delgado, M. Carmen; Harbuzaru, Alexandra (Amer Chemical Soc, 2019)
The first example of an n-type [1]benzothieno[3,2-b][1]benzothiophene (BTBT)-based semiconductor, D-(PhFCO)-BTBT, has been realized via a two-step transition metal-free process without using chromatographic purification. Physicochemical and optoelectronic characterizations of the new semiconductor were performed in detail, and the crystal structure was accessed. The new molecule exhibits a large optical band gap (similar to 2.9 eV) and highly stabilized (Delta E-LUMO = 1.54 eV)/pi-delocalized lowest unoccupied molecular orbital (LUMO) mainly comprising the BTBT pi-core and in-plane carbonyl units. The effect of out-of-plane twisted (64 degrees) pentafluorophenyl groups on LUMO stabilization is found to be minimal. Polycrystalline D(PhFCO)-BTBT thin films prepared by physical vapor deposition exhibited large grains (similar to 2-5 mu m sizes) and layer-by-layer stacked edge-on oriented molecules with an in-plane herringbone packing (intermolecular distances similar to 3.25-3.46 angstrom) to favor two-dimensional (2D) source-to-drain (S -> D) charge transport. The corresponding TC/BG-OFET devices demonstrated high electron mobilities of up to similar to 0.6 cm(2)/V.s and I-on/I-off ratios over 10(7)-10(8). These results demonstrate that the large band gap BTBT pi-core is a promising candidate for high-mobility n-type organic semiconductors and, combination of very large intrinsic charge transport capabilities and optical transparency, may open a new perspective for next-generation unconventional (opto)electronics.
Keywords: Thin-Film Transistors; Charge-Transport Parameters; Molecular-Orbital Methods; Organic Semiconductors; High-Performance; Materials Design; Polymer Semiconductors; Thiophene Oligomers; Crystal-Structure; Building-Blocks